2019
DOI: 10.2147/ndt.s210757
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Eye Movement Desensitization and Reprocessing (EMDR) on the severity of suicidal thoughts in patients with major depressive disorder: a randomized controlled trial</p>

Abstract: ObjectiveDepression is a major risk factor for suicide and more than 90% of people who attempt suicide suffer from depression. The present study aimed to investigate the effect of eye movement desensitization and reprocessing (EMDR) therapy on the severity of suicidal thoughts in patients with major depressive disorder.Study designRandomized Clinical Trial.MethodsThis clinical trial was performed on 70 people with major depressive disorder who exhibited suicidal thoughts. The patients were selected via conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Despite this, there is widespread evidence for the effectiveness of Cognitive Behavioural Therapy (CBT) with individuals who are suicidal [8][9][10][11][12] and Dialectical Behavioural Therapy (DBT) [13][14][15]. Eye Movement Desensitisation and Reprocessing (EMDR) itself occurred twice in the literature [16,17] with Solution Focused Therapy [18][19][20] reporting some encouraging results both individually and within groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, there is widespread evidence for the effectiveness of Cognitive Behavioural Therapy (CBT) with individuals who are suicidal [8][9][10][11][12] and Dialectical Behavioural Therapy (DBT) [13][14][15]. Eye Movement Desensitisation and Reprocessing (EMDR) itself occurred twice in the literature [16,17] with Solution Focused Therapy [18][19][20] reporting some encouraging results both individually and within groups.…”
Section: Introductionmentioning
confidence: 99%
“…One paper described a retrospective case series of a number of patients who were treated using EMDR within a CRHTT, with the researchers finding that taking a trauma informed approach reduced the risk of suicide and prevented further presentations to a CRHTT [45]. More recently, EMDR has found to reduce the severity of suicidal thoughts in patients with major depressive disorder treated in an inpatient setting [16].…”
Section: Introductionmentioning
confidence: 99%
“…1 The prevalence of major depressive disorder throughout the world is generally estimated at 3% to 6%, 2,3 and the prevalence of this disorder in Iran is reported to range from 5.69% to 73.3%. 4 Depression is a strong predictor of impaired quality of life in adults. 5,6 The results of previous studies suggested that even mild levels of depression are associated with a significant decrease in quality of life in adults.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 One of the new techniques is the eye movement desensitization and reprocessing (EMDR), in which the therapist asks the patient to recall disturbing memories as they move their eyes, and as a result, the level of arousal is reduced and thoughts are reorganized. 4 EMDR therapy is an empirically validated trauma intervention which can be effective in treating psychological trauma. 4 The results of Gauhar YW (2016) study on the efficacy of EMDR in the treatment of depression showed that this technique was effective in treating depressive symptoms in patients with major depressive disorder, and improved their quality of life and unpleasant thoughts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation